Study of Gender Differences in Health Promoting Behaviors for a Sample of Students Attending Institute of Technology, Baquba - Noaman, aqeel; dhahir, nasir (Iraqi National Journal of Nursing Specialties, 2016)
Objective: To find out any gender differences in health promoting behaviors for a sample of students attending Institute of Technology/ Baquba. Methodology: An analytical, cross-sectional study conducted randomly for a sample of students attending Technical Institute/ Baquba, during the period from 10th November 2015 to 10th April 2016. A questionnaire used to collecting data, this questionnaire was consisted from two domains related to health promoting behaviors including (Dietary domain and domain of some daily life activities like sleep duration, rise time, bedtime and walking period per week). The questionnaire distributed randomly on students during break between lectures and then collected from the students after being completed. The data analyzed using SPSS (Version.18). Variables were presented as number, percent and mean. The t-test was used to measure the level of significance. Results: The results of the study showed that the rates of consuming breakfast daily (70.1%) and regularity in food meals (52.8%) were significantly higher among male students. This study revealed that the rate of students depended on variety of foods was higher among females (77.6%) than males (68.7%). The mean daily number of sleep duration was significantly longer among female students (7.31) than males (6.92), mean daily rise time (6:35) minutes was significantly earlier among female students and mean daily bedtime (10:35) was significantly earlier among female students than males, the period of walking per week was significantly longer among female students (37:61) minutes. Recommendations: Implantation the educational programs to increase student’s knowledge toward health promoting behaviors and encouraging them to application these behaviors in their daily life.